Decision Support System for Determining Suppliers to Purchase Goods using the Analytical Hierarchy Process Method at PT. Nippon Indosari Corpindo, Tbk - Sihar Sihite (Institute of Computer Science, 2019)
PT. Nippon Indosari Corpindo, Tbk is one of the companies engaged in the industry where the supply and receipt of goods or materials and support in the running of the production process is the most important thing in the process of running this company. That is why in accepting every item from the supplier, it must be well determined and designed to expedite every process, both production and processing inside. Decision support system that can process all data related to computerized supplier performance in order to get better results is of course using the AHP (Analytical Hierarchy Process) method. Decision support systems by mixing several calculation methods are expected to produce good results and are suitable for determining suppliers with outranking systems so that a viable supplier can be sorted by the best value.